New records of rare species in the Mediterranean Sea (May 2020) - GEROVASILEIOU, VASILIS; AKYOL, OKAN; AL-HOSNE, ZINAH; ALSHIKH RASHEED, REEM; ATAÇ, EYLUL; BELLO, GIAMBATISTA; ĆETKOVIĆ, ILIJA; CORSINI-FOKA, MARIA; CROCETTA, FABIO; DENITTO, FRANCESCO; GUIDETTI, PAOLO; GÜL, BENAL; et al. (Mediterranean Marine Science, 2020)
This Collective Article presents information about 17 taxa belonging to four Phyla (one Cnidaria, two Arthropoda, four Mollusca, and ten Chordata) and extending from the Western Mediterranean to the Levantine Sea. The new records were reported from nine countries as follows: Algeria: first published records of the clingfishes Apletodon dentatus and Lepadogaster lepadogaster after 1955; France: first record of the tripletail Lobotes surinamensis in French Mediterranean waters; Italy: new records of the rare bonito Orcynopsis unicolor and the recently described nudibranch Elysia rubeni from Sicily; first records of the parasitic cirriped Sacculina eriphiae and the nudibranch Dondice trainitoi in the Ionian Sea; first record of the nudibranch Taringa tritorquis in the Mediterranean Sea; first record of the tripletail Lobotes surinamensis in the North Ionian Sea; first documented record of the cephalopod Macrotritopus defilippi in the Adriatic Sea; Slovenia: first record of the Mediterranean endemic cryptobenthic goby Odondebuenia balearica; Montenegro: several recent occurrences of the critically endangered bull ray Aetomylaeus bovinus in the South-eastern Adriatic Sea; Greece: records of the nudibranch Dondice trainitoi in the Eastern Mediterranean Sea; new record of the occurrence of the Mediterranean spearfish Tetrapturus belone from Greece (Rhodes Island); Turkey: recent captures of the vulnerable ocean sunfish Mola mola, caught by purse-seine, in the Aegean Sea and the Dardanelles; new record of the luvar Luvarus imperialis along the Aegean coast of Turkey; Cyprus: first record of the habitat-forming hydroid Lytocarpia myriophyllum, often in considerable densities; first confirmed record of the agujon needlefish Tylosurus imperialis; Syria: first record of the decapod Ethusa mascarone.